2013
DOI: 10.1113/jphysiol.2013.259515
|View full text |Cite
|
Sign up to set email alerts
|

AMP‐activated protein kinase regulates nicotinamide phosphoribosyl transferase expression in skeletal muscle

Abstract: Key points• NAD is a substrate for sirtuins (SIRTs), which regulate gene transcription in response to specific metabolic stresses.• Nicotinamide phosphoribosyl transferase (Nampt) is the rate-limiting enzyme in the NAD salvage pathway.• Using transgenic mouse models, we tested the hypothesis that skeletal muscle Nampt protein abundance would increase in response to metabolic stress in a manner dependent on the cellular nucleotide sensor, AMP-activated protein kinase (AMPK).• Exercise training, as well as repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(120 citation statements)
references
References 54 publications
(77 reference statements)
7
112
1
Order By: Relevance
“…It is well known that NAMPT treatment activates various signalling pathways, including PRKA, AKT1, MAPK3/1 and MAPK14, in different cell types (Cheng et al 2011, Brandauer et al 2013, Reverchon et al 2013a, Song et al 2014. We showed that in hen granulosa cells from F1 hierarchical follicles, NAMPT treatment decreased MAPK3/1 phosphorylation after 30 or 60 min of stimulation (Fig.…”
Section: Signalling Pathways Involved In the Nampt Effects In Hen Gramentioning
confidence: 51%
“…It is well known that NAMPT treatment activates various signalling pathways, including PRKA, AKT1, MAPK3/1 and MAPK14, in different cell types (Cheng et al 2011, Brandauer et al 2013, Reverchon et al 2013a, Song et al 2014. We showed that in hen granulosa cells from F1 hierarchical follicles, NAMPT treatment decreased MAPK3/1 phosphorylation after 30 or 60 min of stimulation (Fig.…”
Section: Signalling Pathways Involved In the Nampt Effects In Hen Gramentioning
confidence: 51%
“…Reduced cellular NAD + level is a feature of aging (Gomes et al ., 2013), and a link between NAD + synthesis and AMPK has been suggested (Brandauer et al ., 2013). For these reasons, we next examined the relationships among AMPK, NAD + synthesis and senescence.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, we displayed the direct association of the downregulated NAD + synthesis, particularly involving its salvage pathway, with senescence, and also the regulatory effect of AMPK on NAD + synthesis. In the fact, consistent results have been reported by others (Yoshino et al ., 2011; Brandauer et al ., 2013;). In addition to the salvage pathway of NAD + synthesis, we also preliminarily addressed the impact on the de novo pathway of NAD + synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, AMPK activation leads to an increase in cellular NAD + levels, possibly by increasing Nampt expression. 109,110 Pharmacological or physiological activation of AMPK increased NAD + levels to coordinately enhance SIRT1 activity, leading to the deacetylation and altered transactivity of downstream SIRT1 targets: peroxisome proliferator-activated receptor-γ coactivator 1α (PGC-1α) and forkhead transcription factors FOXO1 and FOXO3a. 94 These changes in transcription factor deacetylation and consequent activity elevate the expression of mitochondrial and lipid oxidation genes in low glucose 111 and may represent a mechanism by which gene programs are poised for response to energy demands.…”
Section: Sensing Metabolic Variationsmentioning
confidence: 99%